SINTESIS DAN KARAKTERISASI BENTONIT - Asep Supriatna, ; Ahmad Mudzakir, ; Adam Nugraha, (Matematika dan Sains, 2010)
Research about modification of bentonite using fatty imidazolinium had been done. Three kind fatty imidazolinium iodide compound succeeded to be synthezed using microwave irradiation method with various R substituents, namely 2-cis-oleil-imidazolinium iodide (surf1) with R = cis-ù-9-CH3(CH2)16-CH2-, 2-stearil-2-imidazolinium iodide (surf2) with R = CH3(CH2)16-CH2-, and 2-palmitil-2-imidazolinium iodide (surf3) with R = CH3(CH2)14-CH2-. Their characteristics were analyzed using FTIR and TG/DTA. Thermal stability analysis showed that Stear-Imz/NaMMT, Pal-Imz/NaMMT , and cis-Ole-Imz/NaMMT dicomposed at 441,9oC; 406,9oC; and 441,8 oC, respectively.3(CH2)16-CH2-, 2-stearil-2-imidazolinium iodide (surf2) with R = CH3(CH2)16-CH2-, and 2-palmitil-2-imidazolinium iodide (surf3) with R = CH3(CH2)14-CH2-. Their characteristics were analyzed using FTIR and TG/DTA. Thermal stability analysis showed that Stear-Imz/NaMMT, Pal-Imz/NaMMT , and cis-Ole-Imz/NaMMT dicomposed at 441,9oC; 406,9oC; and 441,8 oC, respectively.